Obtaining morphometric variables from gullies using two methods of interpolation laser scanner data: the case study of Vassouras, Brazil - de Oliveira, Carlos Magno Moreira; Francelino, Márcio Rocha; de Mendonça, Bruno Araujo Furtado; Ramos, Isabela Queiroz (Journal of mountain science, 2020)
Gully erosion is a worldwide problem of land degradation and water quality, and it is also frequent in Brazil. Typically, anthropic influence is the major driver of gully evolution. To study and monitor gullies it is necessary to use specific instruments and methods to obtain accurate information. The objective of this study was to use Terrestrial Laser Scanning (TLS) to create digital elevation model (DEM) accurately and define morphometric variables that characterize gullies in a mountainous relief. Two different interpolations were evaluated using the Topogrid and GridSurfaceCreate algorithms to elaborate DEM. Topographic profile for gullies was used to assess modeling quality. The DEM of the Gully 1 (G1) from the Topogrid algorithm estimated soil loss of 49%, whereas the GridSurfaceCreate algorithm estimated a soil loss of 97%, in a period of 1 year. The estimated soil loss for the Gully 2 (G2) was 14% from the Topogrid, and 8% from the GridSurfaceCreate algorithm. The GridSurfaceCreate algorithm underestimated the volume to area ratio for G2 due to a failure on interpolating a region of low point representativity. The Topogrid algorithm represented better the terrain irregularities, as observed through the topographic profiles traced in three regions of G1 and G2. Statistical analysis showed that the GridSurfaceCreate algorithm presented lower accuracy in estimating elevations. The underestimation trend of this algorithm was also observed in G2. The gullies showed considerable soil losses, which may reduce the areas suitable for agricultural activities, and silting up of water courses. The Topogrid algorithm presented satisfactory results, denoting great potential to produce morphometric data of gullies.